"y^{\\mathrm{iv}}-2y'''+2y''=3e^{-x}+2e^{-x}x+e^{-x}\\sin x"
To determine the general solution needed find a complementary and partial solutions. First, determine a partial solution.
Rewrite the right part of the equation as
"f(x) = (3+2x)e^{-x} + e^{-x}\\sin x"
Therefore, a partial solution of the equation have a form
"y_p(x) = (A+Bx)e^{-x} + e^{-x}(C\\sin x + D\\cos x)"
Find the derivatives.
"y'_p = Be^{-x} - (A+Bx)e^{-x} - e^{-x}((C+D)\\sin x - (C-D)\\cos x) \\\\\ny''_p = -2Be^{-x} + (A+Bx)e^{-x} + e^{-x}(2D\\sin x - 2C\\cos x) \\\\\ny'''_p = 3Be^{-x} - (A+Bx)e^{-x} + e^{-x}((2C-2D)\\sin x + (2C+2D)\\cos x) \\\\\ny^{\\text{iv}}_p = -4Be^{-x} + (A+Bx)e^{-x} - e^{-x}(4C\\sin x +4D\\cos x)"
Substituting these into the equation, obtain
"-14Be^{-x} + 5(A+Bx)e^{-x} + e^{-x}((8D-8C)\\sin x - (8D + 8C)\\cos x) \\\\= 3e^{-x}+2xe^{-x}+e^{x}\\sin x"
Rewrite the left part.
"(5A-14B)e^{-x} + 5Bxe^{-x} + e^{-x}((8D-8C)\\sin x - (8D + 8C)\\cos x) \\\\= 3e^{-x}+2xe^{-x}+e^{x}\\sin x"
Therefore,
"5A-14B=3\\\\\n5B=2\\\\\n8D-8C=1\\\\\n-8D-8C=0"
Solving these linear system, get that "A= \\frac{43}{25}, B = \\frac{2}{5}, C = -\\frac{1}{16}, \\text{ and } D = \\frac{1}{16}."
Thus, the partial solution is
"y_p(x)=\\left(\\frac{43}{25} + \\frac{2}{5}x \\right)e^{-x} + e^{-x}\\left( \\frac{1}{16}\\cos x - \\frac{1}{16}\\sin x \\right)"
Now, determine a complementary solution. Solve the characteristic equation.
"\\lambda^4 - 2\\lambda^3 + 2\\lambda^2=0\\\\\n\\lambda^2(\\lambda^2 - 2\\lambda + 2) =0" This equation have the roots "\\lambda = 0 \\text{(multiplicity 2) and } \\lambda = 1 \\pm i." Therefore, the complementary solution is
"y_c(x) = C_1 + C_2x + C_3e^x\\cos x + C_4e^x\\sin x" So, the genaral solution is
"y(x) = C_1 + C_2x + C_3e^x\\cos x + C_4e^x\\sin x \\\\+ \\left(\\frac{43}{25} + \\frac{2}{5}x \\right)e^{-x} + e^{-x}\\left( \\frac{1}{16}\\cos x - \\frac{1}{16}\\sin x \\right)"
Comments
Leave a comment